Geological Rating for D-Slope - Omar, Husaini; Daud, Mohamed; Mustapha, Norwati; Md. Yusof, Zainuddin; Osman, M. R.; M., Ratnasamy (Universiti Putra Malaysia Press, 2001)
The purpose of this paper is to present the development of Geological Rating (GR) to carry out slope assessment. In this study, the D-5lope has been developed using geological, hydrological and geotechnical data to evaluate the potential failure of slopes. The geological complexity, the scale of the instability phenomena and the high number of interacting factors complicate most the natural and cut slope analysis. In order to be able to have a structured approach to such complexity, a comprehensive method based on the Geological Rating (GR) is proposed. A total of fourteen (14) parameters (12 geological parameters and 2 hydrological parameters) relating to the slopes have been considered. The slopes are divided into four categories: (I) Not Dangerous Slope (NOS), (II) Slightly Dangerous Slope (SDS), (III) Moderately Dangerous Slope (MOS) , and (IV) Highly Dangerous Slope (HDS). The definitions of these categories are discussed.